"One-pot" synthesis of amidoxime via Pd-catalyzed cyanation and amidoximation1. Issue 9 (7th March 2015) - Yang, Chu-Ting; Han, Jun; Liu, Jun; Gu, Mei; Li, Yi; Wen, Jun; Yu, Hai-Zhu; Hu, Sheng; Wang, Xiaolin
<x xml:space="preserve">Abstract</x> "One-pot" synthesis of amidoxime was developed for studies on the interactions between amidoxime and uranyl.